Diagnosis of single‐phase open‐line fault in three‐phase PWM rectifier with LCL filter. Issue 6 (1st April 2016) - Wu, Fengjiang; Sun, Dongyang; Duan, Jiandong
Abstract : In this study, the transient process when the single‐phase open‐line fault (SPOLF) occurs in the three‐phase AC–DC pulse width modulation rectifier with LCL filter (LCL‐PWMR) is theoretically analysed for the first time and the corresponding diagnosis scheme is proposed. First, the equivalent circuit of the LCL‐PWMR is built and the detected phase voltage (DPV) detected by the three‐phase grid voltage sensors under fault conditions are derived in s ‐domain. The result shows that the DPV in the open‐line phase is not equal to zero, while consists of a fundamental component plus a resonant component with specific frequency. Furthermore, a diagnosis scheme for the SPOLF based on 2‐order band‐pass filter (BPF) connected in series with enhanced phase‐locked loop (EPLL) is proposed. BPF is used to eliminate the fundamental component of the sum of three‐phase DPVs and EPLL to estimate the amplitude of resonant component. Then the SPOLF can be detected when the amplitude of resonant component is beyond the allowed threshold. Furthermore, the adaptability of the proposed diagnosis scheme for the system with different rated power is verified theoretically. Detailed simulations tests based on Matlab/Simulink software and experimental tests are carried out to demonstrate the validity of the theoretical analysis and feasibility of the proposed diagnosis scheme.